2021
DOI: 10.51821/84.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Can we use endocan level to determine severity of pancreatitis?

Abstract: Background and study aims: Endothelial cell specific molecule-1 (ESM-1), also known as endocan, is a soluble proteoglycan secreted by human vascular endothelial cells. In some studies, it has been found that endocan have important effects on cell adhesion, inflammation and angiogenesis. In this study, we aimed to evaluate the endocan level in patients with pancreatitis and the availability of endocan level in determining the severity of the disease. Patients and methods: A total of 42 patients with pancreatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In a study by Albayrak et al, endocan levels, secreted by endothelial cells in response to inflammatory cytokines, were shown to be useful in determining the prevalence of ulcerative colitis characterized by mucosal inflammation and could be beneficial in treatment planning. [23,24] Elevated levels of endocan, similar to SAL-β, were found in both patients with AP and severe ulcerative colitis, aligned with the design of our study. Ultimately, biomarkers identified as elevated in severe pancreatitis can be used for prognosis monitoring and assist clinicians.…”
Section: Discussionsupporting
confidence: 86%
“…In a study by Albayrak et al, endocan levels, secreted by endothelial cells in response to inflammatory cytokines, were shown to be useful in determining the prevalence of ulcerative colitis characterized by mucosal inflammation and could be beneficial in treatment planning. [23,24] Elevated levels of endocan, similar to SAL-β, were found in both patients with AP and severe ulcerative colitis, aligned with the design of our study. Ultimately, biomarkers identified as elevated in severe pancreatitis can be used for prognosis monitoring and assist clinicians.…”
Section: Discussionsupporting
confidence: 86%
“…In important diseases such as acute pancreatitis with similar in ammation, studies have shown that the level of endocan increases as the severity of the disease increases [13]. In particular, the study of Çakır et al [14] in infants with necrotizing enterocolitis showed that the endocan increased signi cantly in showing the severity of the disease, opening a new window. The most important nding in the study of Sakuraba et al [15] in 133 patients with ulcerative colitis was that the extent of the disease may affect the correlation between fecal biomarker values.…”
Section: Discussionmentioning
confidence: 99%
“…As the extent and severity of ulcerative colitis increase, inflammatory markers in serum and stool increase. In important diseases such as acute pancreatitis with similar inflammation, studies have shown that the level of endocan increases as the severity of the disease increases [ 14 ]. In particular, the study of Çakır et al [ 15 ] in infants with necrotizing enterocolitis showed that the endocan increased significantly in showing the severity of the disease, opening a new window.…”
Section: Discussionmentioning
confidence: 99%